Fundamentals of Entrepreneurship (ENT300) Business Plan (Coffee Shop) / Nur Qausar Mohd Yusof - Mohd Yusof, Nur Qausar (2020)
Our company’s name is Nur Qausar Enterprise because this business is sole proprietorship. Nur Qausar Enterprise offers beverage products and services for customers, providing the variety of coffees and deserts that gives high satisfaction for customers. And the kind of coffee business that we want start is a coffee truck because there is still no one who started a coffee business using a truck.